MALIM - a new computational approach of Malay morphology - Sharum, Mohd Yunus; Abdullah, Muhammad Taufik; Sulaiman, Md. Nasir; Azmi Murad, Masrah Azrifah; Zainon Hamzah, Zaitul Azma (IEEE, 2010)
Malay is categorized as an Austronesian language, a group which also contains Bahasa Indonesia and Tagalog. Quite number of morphological analyzers has been developed for Malay, including based on two-level formalism, stemming/conflation model, or even specific model. The obvious weaknesses are incompleteness and incapability of handling ambiguity which affect the accuracy of analysis. So we introduced a new technique called S-A-P-I to handle them in our analyzer - MALIM. In this paper we describe about MALIM and the empirical study to its usage. Our results proved that by using our technique increase the accuracy of morphological analysis up to 98.99% which covers 99.99% of sample data. Thus we believe this approach is the most suitable in handling morphological analysis for Malay.